Uji Efektivitas Nutrisi Ab Mix Terhadap Pertumbuhan dan Hasil Tanaman Kale (Brassica Oleraceae Var. Acephala) Kultivar Curly Gruner Pada Sistem Wick Hidroponik - Tiara Widyaputri; Darso Sugiono; Bastaman Syah (Jurnal Ilmiah Wahana Pendidikan, 2021)
The research was carried out at the Karawang Agricultural State Vocational School located on Jl. Surotokunto No.82, Adiarsa Timur, East Karawang, Karawang Regency, West Java. The research was carried out in June 2021 – August 2021. The purpose of this study was to obtain the value of the effectiveness of AB Mix Nutrition on the growth and yield of Kale (Brassica oleraceae var. Acephala) cultivar Curly Gruner in the system Wick Hydroponic. The research method used an experimental method with a single factor Randomized Block Design (RBD). There were 6 treatments and 4 replications, so there were 24 experimental plots. Data were analyzed using analysis of variance and further tested with DMRT at a level of 5%. The parameters of this study were plant height, number of leaves, stem diameter, leaf area. The results showed that in treatment F (2000 ppm) gave the highest yield on plant height of 57.97 cm, and leaf area in treatment F (2000 ppm) of 133.04 cm². In treatment E (1750 ppm) gave the highest yield on the number of leaves of 22.5 strands and on stem diameter with treatment E (1750 ppm) of 11.63 mm